AI’s invisible touch: how effortless browsing shapes customer perception, experience and engagement in online retail - João M. Lopes; Sofia Gomes; Elisabete Nogueira; Tiago Trancoso (Cogent Business & Management)
This study explores the influence of artificial intelligence (AI)-enabled ease of use on customer perception, experience, and engagement in online retail stores. Through a quantitative analysis of 1438 responses from Portuguese consumers, the research reveals that AI-enabled ease of use positively influences customers’ perceived control, concentration, and cognitive enjoyment while browsing online stores. These perceptions, in turn, contribute to the elicitation of awe, which is found to be a crucial mediating factor in the relationship between customer perceptions and purchase intention. The study highlights the significant role of awe in strengthening the link between customer perceptions and purchase intent, rendering previously non-significant direct effects statistically significant. The findings offer valuable implications for online retailers seeking to leverage AI technologies to enhance customer experiences and drive sales. By prioritizing ease of use, cognitive enjoyment, and perceived control, and strategically leveraging the mediating role of awe, retailers can create engaging and memorable online shopping experiences that ultimately translate to increased customer satisfaction and purchase intention.